Intymność w kulturze flirtu i uwodzenia. Czy wirtu@lny seks na zawsze odmieni intymne relacje partnerskie? - Ściupider-Młodkowska, Mirosława (Wydawnictwo Naukowe UAM, 2013)
The article consists of four parts. The first one defines partnership by confronting the ideal proposed by experts of public guides with the contemporary model of relationship between two individuals. The next part presents the new consumer models of intimacy that refer e.g. to analyses of Anthony Giddens, Zygmunt Bauman and Jean Claude Kaufmann. The main doubts constitute the thesis of the text and are included in two questions: 1) Do present partnerships resemble isolation more than intimacy? 2) What changes partners, who become managers of their own fate? The answers are provided in an analysis of reflective intimacy that manifests itself in new virtual relationships, defined as short-lived relations created in the postmodern and ambiguous world. The last part of the article describes a reformulation of intimacy codes towards more electronic, distant and ambivalent models. Contemporary relationships resemble “reflective bargaining”, where partners create for themselves an “ATM love”. By these means people unconsciously tend to hyper-instrumentalise real relations.
Intimacy in the Culture of Flirtation And Seduction. Will Virtual Sex Forever Change Your Intimate Partnership Relations?
Keywords: partnerships; new model of intimacy and sexuality; changes in family values; virtual relationships